The Impact of Financial Resources, Risk Acceptance, Customer Pressure on Financial Technology - Elsye Fatmawati; Nataliana Bebasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study aims to identify the impact of financial resources, risk acceptance, and customer pressure on the adoption of financial technology on bank employees in Jakarta. The research uses a quantitative approach with survey methods and questionnaires as data collection tools. The sample consisted of 75 bank employees randomly selected from several banks in Jakarta. The data collected will be analyzed using the Structural Equation Model (SEM) to test the research hypothesis. The results of this research can provide an area on the factors that influence the adoption of Financial technology by banking employees, and provide recommendations for increasing the acceptance and use of this technology in the banking industry.